Gender Representation in Indonesian ELT Textbooks of Junior High School: A Corpus-Assisted Critical Discourse Analysis - Fidyaningsih, Adhes; Oktavianti, Ikmi Nur (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study explores gender representation in Indonesian English Language Teaching (ELT) textbooks for Junior High School under the Merdeka Curriculum, employing a corpus-assisted Critical Discourse Analysis (CDA) approach. The research identifies gender-related references and analyzes positive and negative character constructions. The findings indicate a persistent gender imbalance, with male references appearing more frequently than female references in categories such as famous names, fictional names, ordinary names, and pronouns. Male characters are often portrayed with a mix of positive and negative traits, while female characters are predominantly depicted in a positive light. The study concludes that while progress has been made, there is still a significant need for more balanced and inclusive gender representation in educational materials. Addressing these imbalances is crucial for creating an equitable learning environment that reflects and promotes gender equality.